Dental Management For Patients With Cardiovascular Disease: A Literature Review - Sidhi Laksono; Indira Khairunnisa Effendi (Jurnal Kesehatan Gigi, 2023)
The high prevalence of heart disease makes dentists often meet patients with this condition. Cardiac disorders commonly encountered in dental practice include hypertension, ischemic heart disease, cardiac arrhythmias, infective endocarditis, and arrhythmias. These patients required special consideration and adequate understanding of the cardiovascular conditions necessary to provide safe and effective dental care. Based on the heart condition, proper modification in dental care is very important. This article will discuss common heart conditions, how these diseases can affect dental care and prophylactic management and treatments that can be done to provide safe and optimal dental care.